Ethnicity, educational level and attitudes contribute to parental intentions about genetic testing for child obesity - Kocken, Paul L. (Springer-Verlag, 2013)
The objective of this paper is to assess parental beliefs and intentions about genetic testing for their children in a multi-ethnic population with the aim of acquiring information to guide interventions for obesity prevention and management. A cross-sectional survey was conducted in parents of native Dutch children and children from a large minority population (Turks) selected from Youth Health Care registries. The age range of the children was 5–11 years. Parents with lower levels of education and parents of non-native children were more convinced that overweight has a genetic cause and their intentions to test the genetic predisposition of their child to overweight were firmer. A firmer intention to test the child was associated with the parents’ perceptions of their child’s susceptibility to being overweight, a positive attitude towards genetic testing, and anticipated regret at not having the child tested while at risk for overweight. Interaction effects were found in ethnic and socio-economic groups. Ethnicity and educational level play a role in parental beliefs about child overweight and genetic testing. Education programmes about obesity risk, genetic testing and the importance of behaviour change should be tailored to the cultural and behavioural factors relevant to ethnic and socio-economic target groups.